Field Trials Reveal Ecotype-Specific Responses to Mycorrhizal Inoculation in Rice - Diedhiou, A.G.; Mbaye, F.K.; Mbodj, D.; Faye, M.N.; Pignoly, S.; Ndoye, I.; Djaman, K.; Gaye, S.; Kane, A.; Laplaze, L.; Manneh, B.; Champion, A. (Public Library of Science, 2016)
The overuse of agricultural chemicals such as fertilizer and pesticides aimed at increasing crop yield results in environmental damage, particularly in the Sahelian zone where soils are fragile. Crop inoculation with beneficial soil microbes appears as a good alternative for reducing agricultural chemical needs, especially for small farmers. This, however, requires selecting optimal combinations of crop varieties and beneficial microbes tested in field conditions. In this study, we investigated the response of rice plants to inoculation with arbuscular mycorrhizal fungi (AMF) and plant growth promoting bacteria (PGPB) under screenhouse and field conditions in two consecutive seasons in Senegal. Evaluation of single and mixed inoculations with AMF and PGPB was conducted on rice (Oryza sativa) variety Sahel 202, on sterile soil under screenhouse conditions. We observed that inoculated plants, especially plants treated with AMF, grew taller, matured earlier and had higher grain yield than the non-inoculated plants. Mixed inoculation trials with two AMF strains were then conducted under irrigated field conditions with four O. sativa varieties, two O. glaberrima varieties and two interspecific NERICA varieties, belonging to 3 ecotypes (upland, irrigated, and rainfed lowland). We observed that the upland varieties had the best responses to inoculation, especially with regards to grain yield, harvest index and spikelet fertility. These results show the potential of using AMF to improve rice production with less chemical fertilizers and present new opportunities for the genetic improvement in rice to transfer the ability of forming beneficial rice-microbe associations into high yielding varieties in order to increase further rice yield potentials.